ANALISIS JUMLAH CARBON FOOTPRINT SEMEN PADA PEKERJAAN PLESTER DINDING PROYEK RUMAH TINGGAL - Marcell Marcell; Basuki Anondho (JMTS: Jurnal Mitra Teknik Sipil, 2023)
In the world of construction, Occupational Health, Safety and Environment (OHS) is very important to do, and in OHS it is not only the occupational health and safety of construction workers that comes first. Environmental health also needs to be considered. One of the environmental pollution that occurs in construction is the carbon footprint. Carbon footprint is greenhouse gas emissions obtained from the calculation of carbon dioxide (CO2) emissions. The ongoing carbon footprint is causing global warming to hit the earth. The process of making cement to managing cement into residential wall plaster, causing carbon footprint. Carbon footprint is reviewed from the cement manufacturing process, cement transportation process, to the management process into residential cement wall plaster. The purpose of this study is to be able to calculate the amount of carbon dioxide (CO2) gas on the plastering of the walls of a residential house. There are differences and deviations in the thickness of the plastering of the walls of each house, therefore the analysis will compare the results of the differences in the thickness of the wall plaster. From the results of the analysis conducted on 5 different houses located in Sunter, North Jakarta, there were only 2 houses that met the threshold value standard of 5.000 ppm or 0,005 Tons / m3. The average emission result for 5 residential projects if the difference in cement wall plaster thickness is not taken into account is 0,005242 Tons / m3, while in reality on the ground it is 0,005381 Tons / m3. Abstrak Dalam dunia konstruksi Keselamatan, Kesehatan Kerja dan Lingkungan (K3L) sangat penting untuk dilakukan, dan dalam K3L bukan hanya kesehatan dan keselamatan kerja para pekerja konstruksi saja yang diutamakan. Kesehatan lingkungan juga perlu untuk diperhatikan. Pencemaran lingkungan yang terjadi dalam konstruksi salah satunya adalah carbon footprint. Carbon footprint merupakan emisi gas rumah kaca yang didapatkan dari perhitungan emisi gas karbon dioksida (CO2). Carbon footprint yang sedang berlangsung menyebabkan pemanasan global yang melanda bumi. Proses pembuatan semen sampai dengan pengelolaan semen menjadi plesteran rumah tinggal, menimbulkan carbon footprint. Carbon footprint ditinjau dari proses pembuatan semen, proses transportasi semen, sampai dengan proses pengelolaan menjadi plesteran rumah tinggal. Tujuan dalam penelitian ini untuk dapat menghitung jumlah gas karbon dioksida (CO2) pada plesteran dinding rumah tinggal. Terdapat adanya perbedaan dan penyimpangan ketebalan plesteran dinding dari tiap masing-masing rumah, oleh karena itu analisis akan membandingkan hasil akibat dari adanya perbedaan dari ketebalan plesteran. Dari hasil analisis yang dilakukan terhadap 5 rumah yang berbeda yang terletak di Sunter Jakarta Utara, hanya terdapat 2 rumah yang memenuhi standar nilai ambang batas sebesar 5.000 ppm atau 0,005 Ton/m3. Hasil rata-rata emisi untuk 5 proyek rumah tinggal jika perbedaan tebal plesteran tidak diperhitungkan adalah sebesar 0,005242 Ton/m3, sedangkan pada kenyataan di lapangan adalah sebesar 0,005381 Ton/m3.